Pengaruh Return on Asset, Ukuran Perusahaan, Leverage, dan Corporate Social Responsibility terhadap Penghindaran Pajak - Imam Hidayat; Lidya Maulidiyah (Prodi Akuntansi FE Universitas Maritim Raja Ali Haji, 2022)
Tax avoidance is an attempt to reduce the amount of taxes owed by using loopholes contained in applicable tax regulations. This study aims to obtain empirical evidence on the effect of return on assets, corporate size, leverage, and corporate social responsibility on tax avoidance. The population of this study is a consumer goods sector manufacturing company listed on the Indonesia Stock Exchange (IDX) for the period 2016-2019. The method of determining samples from this study is by purposive sampling according to predetermined criteria and obtained samples of as many as 10 companies. The analytical technique used is multiple linear regression. Research shows that return on assets has a negative and significant effect on tax avoidance, while corporate size, leverage and corporate social responsibility have a positive and significant effect on tax avoidance. Keywords : Return On Asset, Coporate Size, Leverage, Corporate Social Responsibility, Tax Avoidance